Low dose unfractionated heparin with low dose aspirin in treatment of thrombo prophylaxis in utero placental insufficiency: a new vision in heparinization during pregnancy - Madhubala, M.; Kasthuri, C.; Shukul, Mansi; Ali, J. Mohamed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The use of heparin and aspirin in obstetric care has grown considerably since their introduction into clinical practice. Because of the physiological changes of pregnancy, the usage of heparin and optimal dosage of heparin remains uncertain. Here our institute designed low dose Unfractionated Heparin (5000 IU s/c daily) as thrombo Prophylaxis regimen. To study the outcome of low dose UFH (5000 IU sc /daily) + Low dose aspirin (75 mg oral per day) for thrombo prophylaxis in utero placental insufficiency, in patient with 2 or more abortions. Methods: This retrospective study was conducted in 135 patients with 2 or more abortions as obstetric history. Prophylactic low dose of UFH (5000 IU s/c daily) + LDA 75 mg oral was initiated. The Primary outcome is live birth, and secondary outcomes is Reduced incidence of early onset of gestational hypertension (HT), Intrauterine Growth Retardation (IUGR). Results: Out of 135 women 131 gave live birth, 2 had first trimester abortion and 2 had intrauterine death by 5 to 6 months. PIH was higher in patients with more than 30 years of age. Conclusions: In our Retrospective, data combination of low dose UFH (5000IU s/c) + LDA (75mg oral) is as safe as routine thrombo prophylaxis with good compliance.